2011
DOI: 10.1007/s11745-011-3638-x
|View full text |Cite
|
Sign up to set email alerts
|

Myristic Acid Increases Dihydroceramide Δ4‐Desaturase 1 (DES1) Activity in Cultured Rat Hepatocytes

Abstract: Dihydroceramide Δ4-desaturase 1 (DES1) catalyzes the last step of the de novo ceramide biosynthesis, which consists of the introduction of a trans Δ4-double bond in the carbon chain of the dihydroceramide. It was previously observed that myristic acid binds DES1 through N-myristoylation. This N-terminal modification significantly increased the activity of the recombinant DES1 in COS-7 cells and targeted part of the enzyme initially present in the endoplasmic reticulum to the mitochondrial outer membrane, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…As is the case with b5R, DES1 is dually targeted to the ER and mitochondria, and it was shown that protein N -myristoylation favors to localization to the mitochondria [26]. In addition, it was also demonstrated that protein N -myristoylation positively affected the enzymatic activity of DES1 [25], [27].…”
Section: Introductionmentioning
confidence: 88%
“…As is the case with b5R, DES1 is dually targeted to the ER and mitochondria, and it was shown that protein N -myristoylation favors to localization to the mitochondria [26]. In addition, it was also demonstrated that protein N -myristoylation positively affected the enzymatic activity of DES1 [25], [27].…”
Section: Introductionmentioning
confidence: 88%
“…on DES1/DES2 activity or expression. A body of evidence also suggests a role for DES1 myristoylation in the control of activity (44,79,80).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Although the initial steps and the majority of de novo ceramide formation clearly take place in the ER ( 7,8 ), the enzymes involved in the fi nal steps of ceramide formation (CerS and dihydroceramide desaturase) were also found in mitochondria ( 14,84,85 ). Moreover, Ardail and colleagues provided evidence that MAM, the specialized ER compartment involved in the transfer of lipids and Ca 2+ between the ER and mitochondria (86)(87)(88), contains glucosylceramide and lactosylceramide synthases which tunnel glycosphingolipids to mitochondria ( 89 ).…”
Section: Lactosylceramide Suppresses Mitochondrial Respiration and Dementioning
confidence: 99%